Improving the delivery process of water and wastewater treatment plant public projects through the use of IPD principles - Abi Shdid, Caesar (2015)
The complex nature of the processes performed by water and wastewater treatment facilities render the planning, design, and construction management of such facilities rather complicated tasks that require specialized expertise. Existing data shows that nine out of every ten such projects in North America incur as much as 24% cost overruns, and between forty and fifty percent of them are behind schedule. The currently used project delivery methods of such public projects must therefore be re-assessed to find ways to alleviate these chronic shortcomings. Data for several water and wastewater projects delivered using the traditional Design-Bid-Build (DBB) delivery method is collected from water utilities in South Florida. The collected data is used to compute key performance indicators (KPIs) of these projects. A selected array of Integrated Project Delivery (IPD) principles, that can be readily implemented to public projects without violating established policies for publicly-owned projects, are implemented in two case study projects, and their respective performance is measured using the same KPIs. The KPIs obtained are compared using performance metric formulae. The data analysis shows enhancements in the performance of the delivery of public water and wastewater construction projects through the implementation of certain aspects of IPD. It is recommended for water and wastewater owners, designers, builders, and operators to have a clear mission and vision to implement more IPD principles to the traditional delivery of public projects. This will allow for faster, smoother, and cheaper installation of such facilities. Governments should also find ways to incorporate certain IPD principles into public water and wastewater projects’ bidding and contractual policies and guidelines.